Ocean : a visual encyclopedia - Woodward, John, 1954- (DK Publishing, 2015)
Explore the hidden depths of the ocean with this stunning visual encyclopedia for kids. Ocean: A Children's Encyclopedia reveals the secrets of the seas through stunning images and beautiful photography to engage and educate kids. From the Arctic to the Caribbean, tiny plankton to giant whales, sandy beaches to the deepest depths, Ocean: A Children's Encyclopedia let's your child discover the mysterious world beneath the waves. Packed with fun facts for kids, this encyclopedia will dazzle your child covering everything from sea creatures and ocean birds to the Great Barrier Reef. Topics are presented through a combination of fun graphics, interesting fact-boxes and high-quality photographs. Look up an individual subject for school projects or curious minds can read from beginning to end!